Variations on a theme: Labeling patients as persons, the nursed, or client in nursing - Feni Betriana; Rozzano C. Locsin (Belitung Raya Foundation, Indonesia, 2022)
The debate regarding the variation of names used for labeling the patient in a nursing care situation has always existed in nursing. Names such as patient, client, person, and nursed have been used widely among healthcare disciplines, including nursing. However, does the use of any of these identifying terms establish the appropriate identification of the nurse and the persons being nursed in a nursing care situation participating in a mutual relationship? This editorial aims to address the varieties and rationales of identifying persons participating in or receiving nursing care. Among these terms, “person” describing human beings underscores personhood, allowing nurse-nursed relations to foster, support, celebrate, and affirm living the meaning of what matters most to one’s life. Therefore, it will be advantageous to nursing practice if the term “person being nursed” is the relevant descriptor to be considered as the primary label.